2010
DOI: 10.1021/jp910777r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sulfur Poisoning on the NOxUptake of a NOxStorage and Reduction (NSR) Model Catalyst

Abstract: Toward obtaining a more detailed understanding of the influence of SO x poisoning on the mechanism of NO x uptake on a NO x storage and reduction (NSR) catalyst, we have performed a model study under ultrahigh vacuum (UHV) conditions. A supported model catalyst based on a thin well-ordered alumina film grown on a NiAl(110) single crystal is used onto which BaO and Pd particles are deposited. Time-resolved (TR) infrared reflection absorption spectroscopy (IRAS) is applied to identify the species formed during N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
5
15
1
Order By: Relevance
“…The introduction of 10 torr 15 NO at room temperature afforded the spectrum shown in Figure 23 (curve a). Similar adsorption characteristics as those of 14 NO presented, and two main bands and a shoulder with narrow FWHM were observed at 1842, 1826, and 1853 cm −1 . The positions of these bands showed about 30 cm −1 red shift compared with those of 14 NO, which confirmed that these adsorbed bands were from the NO species.…”
Section: Isotopic 15 No Adsorptionsupporting
confidence: 74%
See 1 more Smart Citation
“…The introduction of 10 torr 15 NO at room temperature afforded the spectrum shown in Figure 23 (curve a). Similar adsorption characteristics as those of 14 NO presented, and two main bands and a shoulder with narrow FWHM were observed at 1842, 1826, and 1853 cm −1 . The positions of these bands showed about 30 cm −1 red shift compared with those of 14 NO, which confirmed that these adsorbed bands were from the NO species.…”
Section: Isotopic 15 No Adsorptionsupporting
confidence: 74%
“…Typical model of an NSR catalyst is Pt-Ba/Al 2 O 3 , which was developed by Toyota's research group [6][7][8][9]. Although considerable amounts of experimental and theoretical investigations of Pt-Ba/Al 2 O 3 have been conducted, serious problems still remain with respect to sulfur poisoning [6,[13][14][15][16]. Meanwhile, high-NO x storage NSR catalysts are desirable because increasing NO x storage capacity can decrease the necessary catalyst and, in turn, decrease the amount of precious metals required and the cost.…”
Section: Introduction 1overview Of the Development On Nsr Catalystsmentioning
confidence: 99%
“…Replacement effects of this kind are further related to stability concerns in IL-based catalysts. One example could be the poisoning of a SCILL system, where the adsorption of large molecular reactants might block the reactive sites on the surface, irreversibly lowering the catalytic activity over time, similar to poisoning of Pt catalysts by sulfur or other nonreactive species [60,[195][196][197][198]. Another example would concern SILP systems based on large molecules (like metalloporphyrin derivates) as catalytic centers [171].…”
Section: Replacement Of Ionic Liquids By Porphyrins At Metal Interfacesmentioning
confidence: 99%
“…Because of similar IR band positions for both types of adsorbates with their mono- or multidentate bonding character a clear and unambiguous discrimination between them is impossible on the basis of the experimental data presented. 55 The presence of sulfur in a positive oxidation state, however, was confirmed with XPS and is further strengthened by FT-IR spectroscopy.…”
Section: Resultsmentioning
confidence: 88%